Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/diagnostics12020423
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Nutritional Index and Lung Immune Prognostic Index as Prognostic Predictors for Combination Therapies of Immune Checkpoint Inhibitors and Cytotoxic Anticancer Chemotherapy for Patients with Advanced Non-Small Cell Lung Cancer

Abstract: Combination therapy with immune checkpoint inhibitors and cytotoxic chemotherapies (chemoimmunotherapy) is associated with significantly better survival outcomes than cytotoxic chemotherapies alone in patients with advanced non-small cell lung cancer (NSCLC). However, there are no prognostic markers for chemoimmunotherapy. The prognostic nutritional index (PNI) and lung immune prognostic index (LIPI) are prognostic biomarkers for immune checkpoint inhibitor (ICI) monotherapy or cytotoxic chemotherapies. Thus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…So we can infer that there may be a difference in the staging of lung cancer, it is an important source of heterogeneity. Five studies [ 14 , 15 , 17 , 19 , 20 ] were conducted on NSCLC alone, 1 study [ 16 ] was conducted on SCLC, and 1 study [ 21 ] did not distinguish between NSCLC and SCLC. It is known that the OS of SCLC is much worse than that of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…So we can infer that there may be a difference in the staging of lung cancer, it is an important source of heterogeneity. Five studies [ 14 , 15 , 17 , 19 , 20 ] were conducted on NSCLC alone, 1 study [ 16 ] was conducted on SCLC, and 1 study [ 21 ] did not distinguish between NSCLC and SCLC. It is known that the OS of SCLC is much worse than that of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that the presence of sarcopenia and cancer cachexia in advanced NSCLC may affect the efficacy of immunotherapycontaining regimens. In addition, inflammatory/ prognostic scores, such as modified Glasgow prognostic score, prognostic nutritional index, nutritional index, and neutrophil/lymphocyte ratio, are associated with cancer cachexia (41,42) and prognosis of advanced NSCLC patients (42)(43)(44)(45).…”
Section: Efficacy Of Icis In Advanced Nsclc Patients With Cancer Cach...mentioning
confidence: 99%
“…In fact, a combined NLR-HGB biomarker can predict ICI response, showing that patients with pre-treatment high NLR and low HBG present worse OS (N= 123, HR = 2.6, p = 3.5 × 10 −5 ) [ 47 ]. Tanaka et al recently showed that the Lung Immune Prognostic Index (LIPI) could predict resistance to ICI in patients with previously treated advanced NSCLC, finding that in patients with low PD-L1 treated with chemoimmunotherapy (N = 237), LIPI can especially predict both PFS (HR, 2.75; p < 0.001) and OS (HR, 2.01; 95% CI, 1.28–3.15; p < 0.001) [ 48 ]. In addition, the pre-treatment levels of LIPI, combined with N ≥ 4 and high levels of serum Lactate Dehydrogenase (LDH), negatively correlated with the PFS (N = 113, p = 0.0119) [ 49 ].…”
Section: Circulating Immune Cellsmentioning
confidence: 99%